Electromyographic validation of the deltoideus (anterior portion) and pectoralis major (clavicular portion) muscles in pull-over exercises - Bull, Marilena Longo [UNESP]; Ferreira, M. I.; Vitti, M. (My University, 2007)
The electromyographic activity of the deltoideus (anterior portion) and pectoralis major (clavicular portion) muscles was analyzed in 24 male volunteers in two different modalities of pull-over exercises. The PMC activity varied from weak to moderate in both modalities, while the DA activity was moderate in the pull-over and strong in the pull-over with bent arms exercises.
Keywords: Electromyography; Exercises; M. deltoid; M. pectoralis major; Physical conditioning; adolescent; adult; arm exercise; controlled study; deltoid muscle; electromyography; exercise physiology; human; human experiment; male; muscle contraction; muscle exercise; normal human; pectoralis major muscle; validation process; volunteer; Action Potentials; Adolescent; Adult; Clavicle; Exercise; Humans; Male; Muscle, Skeletal; Pectoralis Muscles; Reference Values